1999
DOI: 10.1111/1540-6229.00771
|View full text |Cite
|
Sign up to set email alerts
|

Do Real Estate Prices and Stock Prices Move Together? An International Analysis

Abstract: The relationship between stock prices and real estate prices has been the subject of substantial debate in both the academic and practitioner literatures. Existing studies have focused on the time series of stock and real estate returns using data from a single country, such as the U.S. By necessity, these studies examine return and price changes over short intervals, creating a bias when property values are smoothed from year to year. Using data from 17 different countries over 14 years, this paper examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
136
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(147 citation statements)
references
References 9 publications
6
136
2
3
Order By: Relevance
“…Third, researchers in earlier, less-sophisticated studies concentrate on the relationship between real estate and stock markets through standard correlation analysis (Ibbotson and Siegel, 1984;Hartzell, 1986;Eichholtz and Hartzell, 1996;Worzala and Vandell, 1993;Quan and Titman, 1999). 5 Although correlations can provide information about co-movement of variables, it does not inform us about long-run relationships (i.e., cointegration) and/or the lead-lag relationships (Granger causality) between the markets.…”
mentioning
confidence: 99%
“…Third, researchers in earlier, less-sophisticated studies concentrate on the relationship between real estate and stock markets through standard correlation analysis (Ibbotson and Siegel, 1984;Hartzell, 1986;Eichholtz and Hartzell, 1996;Worzala and Vandell, 1993;Quan and Titman, 1999). 5 Although correlations can provide information about co-movement of variables, it does not inform us about long-run relationships (i.e., cointegration) and/or the lead-lag relationships (Granger causality) between the markets.…”
mentioning
confidence: 99%
“…Liu and Mei (1992), Ambrose et al (1992), Ling and Naranjo (1999), Quan and Titman (1999) and Peng and Schulz (2013) found that the two markets are correlated while the results of Ibbotson and Siegel (1984), Miles et al (1990) and Liu et al (1990) suggest that the two markets are segmented and do not display significant long-term correlation.…”
Section: Introductionmentioning
confidence: 91%
“…The only study performed jointly for developed and developing countries (Čeh Časni, Vizek, 2014) also arrives at the same conclusion, but emphasise that integration decreased substantially after 2008 financial meltdown. In contrast, alternative stream of literature finds little, if any, evidence of integration between real estate and stock markets (see Geltner, 1990;Liu et al 1990;Quan and Titman, 1999;and Wilson et al, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%